Identification of Potential Biomarkers and Immune Cell Signatures in COVID-19 Myocarditis Through Bioinformatic Analysis - Yongfei Song; Xiaofei Wang; Dongdong Tong; Xiaoyan Huang; Xiaojun Jin; Chuanjing Zhang; Jianhui Liu; Bo Guo; Chen Huang; Jiangfang Lian (Cardiology Research and Practice)
Conclusion: B2M and C3 have been identified as potential biomarkers for viral myocarditis, providing valuable insights for future investigations into the pathogenesis of COVID-19-associated myocarditis.